Pelatihan Digital Marketing serta Optimalisasi TikTok Shop untuk Pelaku UMKM Taman Cibinong Asri Bogor - Rosmita Rosmita; Sismadi Sismadi; Indah Purwandani; Devy Sofyanty (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
TikTok Shop is a social e-commerce platform where vendors can sell products to TikTok users. Users can then purchase items in various conditions with this program. Additionally, sellers can post and save product details and listings to promote to TikTok users.The purpose of carrying out this Community Service activity is to optimize marketing activities for SMEs digitally so that SMEs products in Taman Cibinong Asri Bogor can cover a wider scope. Community Service activities carried out by organizing socialization and training for all SME actors. In the counseling session, participants were given direct practice in creating a TikTok Shop account, uploading products and creating promotional content. The results of the activity show that participants have a good understanding of digital technology, especially TikTok Shop. Participants are also able to create a TikTok Shop account and upload their products. However, participants still need to improve their skills in creating interesting promotional content.